Perú y Brasil entre el Pacífico y el Atlántico: Espacio surandino e integración sudamericana - Chuquihuara, Luis (1995)
In 1909, the "Boundary, Trade and Navigation Treaty" signed between Peru and Brazil, represented by their then chancellors, Hernán Velarde and the Baron of Rio Branco, definitively established the border delimitation between both countries. Said bilateral legal instrument, however, did not modify historical guidelines. Before and after, both states promoted development orientations that dispensed with the Andean-Amazonian axis as a natural space to dynamize and project the neighborhood interrelation. Since the colony and during much of the republican period, the prevailing geopolitical trend, both in Peru and Brazil, was the development of the coastal strips as nuclei of political, economic and social articulation.